'Imbued with the Essence of the Owner': Personhood and Possessions in the Reopening and Reworking of Viking-Age Burials. (2016) - Klevnäs, Alison Margaret
Abstract : This article examines the wide range of grave disturbance practices seen in Viking-age burials across Scandinavia. It argues that the much-debated reopenings at high-profile sites, notably the Norwegian 'royal' mounds, should be seen against a background of widespread and varied evidence for burial reworking in Scandinavia throughout the first-millennium AD and into the Middle Ages. Interventions into Viking-age graves are interpreted as disruptive, intended to derail practices of memory-creation set in motion by funerary displays and monuments. However, the reopening and reworking of burials were also mnemonic citations in their own right, using a recurrent set of practices to make heroic, mythological, and genealogical allusions. The retrieval of portable artefacts was a key element in this repertoire, and in this article I use archaeological and written sources to explore the particular concepts of ownership which enabled certain possessions to work as material citations appropriating attributes of dead persons for living claimants.